Miscibility of Crystalline/Amorphous/Crystalline Biopolymer Blends from PLLA/PDLLA/PHB with Additives. Issue 1 (2nd January 2019) - El-Hadi, Ahmed M.
ABSTRACT: Miscibility of three biopolymers (PLLA, PDLLA and PHB) blends were investigated by POM, WAXD, FTIR, and DSC. DSC verified the thermal properties of biopolymer blend with PVAc as a compatibilizer, and TBC as plasticizer. Some change in glass transition temperature (Tg ) of biopolymer blends from 60°C to 0.7°C. The spherulitic morphology of blend 9 changing by addition more PHB (50%), the results dendritic spherulites. The adding PHB to PLLA blends make certain shifting in the diffraction peak from 2 ϑ = 16.9° to 2 ϑ = 16.6° and the carbonyl group shifts from 1752 cm −1 to 1732 cm −1 in blends, demonstrating polar interactions between them.